Respuesta :

Answer:

Option 2 is the right answer.

Step-by-step explanation:

The matrix equation is given by, AX + B = C.

AX = C - B = [tex]\left[\begin{array}{ccc}-42&-20\\5&4\end{array}\right] - \left[\begin{array}{ccc}-7&-9\\4&-1\end{array}\right] = \left[\begin{array}{ccc}-35&-11\\1&5\end{array}\right][/tex].

Let X = [tex]\left[\begin{array}{ccc}x&y\\z&t\end{array}\right][/tex].

Hence, AX = [tex]\left[\begin{array}{ccc}-3&-4\\1&0\end{array}\right] \left[\begin{array}{ccc}x&y\\z&t\end{array}\right] = \left[\begin{array}{ccc}-3x - 4z&-3y - 4t\\x&y\end{array}\right][/tex].

As per the above equation, x = 1, y = 5.

[tex]-3x - 4z = -35\\ -4z = - 32\\z = 8[/tex].

[tex]-3y - 4t = -11\\-4t = 4\\t = -1[/tex].

X = [tex]\left[\begin{array}{ccc}1&5\\8&-1\end{array}\right][/tex]